2021
DOI: 10.36227/techrxiv.17004538.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TFW: Annotated Thermal Faces in the Wild Dataset

Abstract: Face detection and localization of facial landmarks are the primary steps in building many face applications in computer vision. Numerous algorithms and benchmark datasets have been proposed to develop accurate face and facial landmark detection models in the visual domain. However, varying illumination conditions still pose challenging problems. Thermal cameras can address this problem because of their operation in longer wavelengths. However, thermal face detection and localization of facial landmarks in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Regarding the TFW dataset, the authors reported 100% for the indoor set and 97.2% AP for the outdoor set as their best results [24]. In our case, the AnyFace model achieved 100% for the indoor set and 99.2% for the outdoor set without test set augmentation.…”
Section: Results On the Test Setmentioning
confidence: 54%
“…Regarding the TFW dataset, the authors reported 100% for the indoor set and 97.2% AP for the outdoor set as their best results [24]. In our case, the AnyFace model achieved 100% for the indoor set and 99.2% for the outdoor set without test set augmentation.…”
Section: Results On the Test Setmentioning
confidence: 54%
“…Therefore, a limited number of face detection models are available for these cameras. For instance, the YOLOv5 model was used to implement a thermal face detection model [24]. The authors collected 9,982 thermal images and manually annotated 16,509 faces to train the model.…”
Section: Related Workmentioning
confidence: 99%
“…The dataset contains 60,000 images (109,807 annotated faces) for the face detection task. TFW dataset [24] Images Faces Wider Face [22] 32,203 393,703 AnimalWeb [34] 19,079 22,451 iCartoonFace [40] 60,000 109,807 TFW [24] 9,982 16,509…”
Section: A Datasetsmentioning
confidence: 99%